EFFECT OF HONEY AND Lactobacillus delbrueckii subsp. bulgaricus CONCENTRATION ON PROTEIN CONTENT, TOTAL ACIDITY, AND SENSORY QUALITY OF YOGURT - Hidayati, Laras Annisa; Suhartatik, Nanik (Tahta Media Group, 2025)
Jackfruit seeds contain high carbohydrates and protein, so it can be used as an alternative mixture of skim milk in the manufacture of ice cream was used sappan wood as natural colour. This experiment was aimed to determine the melting time and organoleptic test of the ice cream with the addition of jackfruit seeds and sappan wood as natural colour. The method used in this experiment was completely randomized design (CRD) with two factors, namely the first factor were the combination of jackfruit seeds:skim milk (0:100; 25:75; 50:50; 75:25) and the second factor were addition of sappan wood (0; 5; 10 g). The results showed that the lowest melting time was a combination of jackfruit seeds:skim milk (75:25) and the addition of 10 g sappan wood extract for 25 minutes. The results of organoleptic test are extremely diverse and can be accepted by society.